DOES THE COVID-19 PANDEMIC PLAY A ROLE IN CORPORATE GOVERNANCE IN INFLUENCING BANK RISK MANAGEMENT IN INDONESIA (Empirical Study of Bank KBMI 2,3,4 in Indonesia 2017-2022) - Novaldhi, Muhammad Jason; Utomo, Dwi Cahyo (Diponegoro Journal of Accounting, 2024)
This research examines the relationship between the COVID-19 pandemic, corporate governance and risk management of banks in Indonesia. This research has dependent variables, namely market risk, credit risk, liquidity risk, and operational risk with the independent variable good corporate governance. This research uses secondary data originating from the KBMI bank's annual financial reports 2,3,4 for 2017-2022. This research uses the MANOVA (Multivariate Analysis of Variance) method. The findings of this research prove that there is a relationship between COVID-19, corporate governance and bank risk management and also there are differences in risk management, namely market risk, credit risk and liquidity risk which are influenced by corporate governance and the COVID-19 pandemic.